Status Pengelolaan Perikanan dengan Pendekatan Ekosistem (P3E) pada Domain Sumberdaya Ikan untuk Komoditas Udang di Kabupaten Sorong Selatan Provinsi Papua Barat - Diah A. P; Abudarda Razak; Ahmad Fahrizal; Irwanto Irwanto (Jurnal Airaha, 2018)
This study aims as follows: 1) to determine the status of Ecosystems Approach of Fisheries Management (EAFM) in the domain of fish resources for commodities in South Sorong Regency, West Papua Province. The method used in this research is survey method, interview and interview. The results of the study in this study, for the Standard CpUE indicator, Composition of Catching Species and Collapse Range of Fish Resources are still in good status. While the indicators that need to be prioritized for improvement in sustainable management because it has a moderate to bad status, namely Fish Size Trends, Proportion of Yuwana (Juvenile) Fish that have been used and ETP Species. The results of the study show that the management of banana commodities (Penaeus merguiensis) is in good condition with green flag modeling and a mean value of 3.